Восточный бастион: роман / А. А. Проханов - Проханов А. А. (Последний солдат империи, 2007)
Экземпляры: (20141110) / Инвентарный номер: 37941 / Цена: 85.50 / Сис.шифр: Р2 / Авт.знак: П 84 / ГРНТИ: 17 / ББК: 84(2Рос=Рус)6